Dry sliding wear and friction behavior of powder metallurgy FeCoNiAlSi0.2 high-entropy alloys - Lee, Hansung; Sharma, Ashutosh; Ahn, Byungmin (Wear, 2023)
Wear behaviors of the FeCoNiAlSi0.2 high-entropy alloy (HEA) and Si-free FeCoNiAl during the reciprocating sliding wear process were evaluated for automotive piston rings. The HEAs were prepared using on advanced powder metallurgy route to solve the inherent shrinkage porosity and segregation defects during casting, poor densification, and wear resistance of HEAs while reciprocating motion. The morphology, hardness, wear, and friction properties were investigated. FeCoNiAl had biphasic face-centered cubic (FCC) and body-centered cubic (BCC) solid solution structures, whereas FeCoNiAlSi0.2 HEAs had a single BCC solid solution structure. Si addition significantly enhanced the hardness and wear resistance of the HEAs under reciprocating conditions because of the increased solid solution strengthening and lattice distortion effects. The maximum hardness of the FeCoNiAlSi0.2 HEA reached approximately 582 HV, which is higher than that of the equiatomic FeCoNiAl HEA (491 HV). The findings depict that FeCoNiAlSi0.2 maintains better tribological behavior than FeCoNiAl HEA against the tungsten carbide (WC) ball indenter. Oxidative delamination and cracking occurred in the FeCoNiAl/WC pair, whereas a mixed adhesive–abrasive wear mechanism was prominent in the FeCoNiAlSi0.2/WC pair because of the harder BCC solid solution phase. This study explores an effective strategy for enhancing the tribology behavior of automotive piston structures under varying loads and reciprocating dry sliding motions.
Keywords: Automotives; Body-centred cubic; Cubic solid solutions; Dry sliding friction; Dry sliding wear; High entropy alloys; Phases transformation; Sliding wear behaviour; Solid solution structures; Wear and friction; Friction; High entropy alloy; Phase transformation; Powder metallurgy; Wear